Genetic diversity of Sterculia quadrifida in Kupang, Indonesia based on RAPD (Random Amplified Polymorphic DNA) markers - Uslan Uslan; MADE PHARMAWATI (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Uslan, Pharmawati M. 2020. Genetic diversity of Sterculia quadrifida in Kupang, Indonesia based on RAPD (Random Amplified Polymorphic DNA) markers. Biodiversitas 21: 3407-3414. This study aims to determine the genetic diversity of Sterculia quadrifida R.Br. in Kupang based on RAPD markers. Samples of S. quadrifida were collected from the yard and community forest in Kupang City (Sub-districts of Oebobo, Kelapa Lima, Maulafa, and Alak) and mixed forest in the Kupang District (Sub-districts of Kupang Barat, Nekamese, Taebenu, and Fatuleu). DNA was isolated by the CTAB method and amplified by six RAPD primers (OPD-11, OPF-11, UBC-106, UBC-127, UBC-250, and OPB-04). The data were analyzed in the MVSP software using UPGMA method and Nei & Li similarity coefficient. Total of 131 DNA bands ranging from 250-1400 bp was obtained. Populations of S. quadrifida in Kupang were divided into two main clusters and 12 sub-clusters with. The highest genetic diversity was found in Kelapa Lima of 0.1050, while the lowest genetic diversity was found in S. quadrifida population in Fatuleu of 0.0305. The population of S. quadrifida in Kupang has high genetic diversity and also clustered based on their geographical distribution